Implementation of community-based Merdeka Curriculum at MTSN 7 Pesisir Selatan - Ilmita Ilmita (Inovasi Kurikulum, 2024)
One of the Ministry of Religious Affairs' initiatives is the implementation of the Community-Based Merdeka Curriculum (IKM) in madrasah. The aim is for all stakeholders to collaborate to support the independent curriculum implementation in madrasahs. This study aims to identify and obtain information about implementing the independent curriculum at MTsN 7 Pesisir Selatan from the author's perspective as a community member. The method used is descriptive qualitative. The research was conducted at MTsN 7 Pesisir Selatan, and data was collected through observation, interviews, and documentation. The data analysis techniques include data reduction, presentation, and conclusion drawing. Triangulation used to test the data's validity includes source and method triangulation. The results of this study indicate that the community-based independent curriculum implementation at MTsN 7 Pesisir Selatan has been carried out optimally and is ongoing. However, there are still many shortcomings and obstacles in its implementation. The key to the success of the community-based independent curriculum implementation at MTsN 7 Pesisir Selatan lies in the involvement of various stakeholders, including the school principal and teachers, LPTK lecturers, and madrasah education supervisors from the Ministry of Religious Affairs, who are willing to make changes.   Abstrak Salah satu kebijakan Kementerian Agama adalah menginisiasi Implementasi Kurikulum Merdeka (IKM) berbasis komunitas di madrasah, tujuannya supaya semua stakeholder bahu membahu dalam mendampingi penerapan kurikulum merdeka di madrasah. Penelitian ini bertujuan untuk mengidentifikasi dan memperoleh informasi tentang implementasi kurikulum merdeka di MTsN 7 Pesisir Selatan dari kacamata penulis sebagai salah satu anggota komunitas. Metode yang digunakan adalah metode deskriptif kualitatif. Penelitian dilakukan di MTsN 7 Pesisir Selatan dengan pengumpulan data melalui observasi, wawancara dan dokumentasi. Teknik analisis data yang digunakan adalah reduksi data, penyajian data dan penarikan kesimpulan. Triangulasi yang digunakan untuk menguji keabsahan data adalah triangulasi sumber dan metode. Hasil penelitian ini menunjukan bahwa implementasi kurikulum merdeka berbasis komunitas di MTsN 7 Pesisir Selatan telah dilaksanakan dengan optimal dan sedang berlangsung, walaupun dalam pelaksanaannya masih banyak kekurangan dan hambatan. Kunci keberhasilan dari implementasi kurikulum merdeka berbasis komunitas di MTsN 7 Pesisir Selatan adalah adanya keterlibatan berbagai pihak (stakeholder) yaitu kepala sekolah dan para guru, dosen LPTK dan pengawas pendidikan madrasah kementerian Agama yang memiliki kemauan untuk melakukan perubahan. Kata Kunci: kurikulum; implementasi kurikulum; IKM BK; Kurikulum Merdeka